2022
DOI: 10.1002/brb3.2752
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotics prescription and adherence among stroke survivors: A systematic review and meta‐analysis

Abstract: Objectives We aimed to investigate the prescription of antithrombotic drugs (including anticoagulants and antiplatelets) and medication adherence after stroke. Methods We performed a systematic literature search across MEDLINE and Embase, from January 1, 2015, to February 17, 2022, to identify studies reporting antithrombotic medications (anticoagulants and antiplatelets) post stroke. Two people independently identified reports to include, extracted data, and assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 89 publications
3
3
0
Order By: Relevance
“…Our results were broadly consistent with several observational studies conducted in Australia 11 , 17 , 27 and other jurisdictions internationally, 8 , 25 , 31 although not directly comparable due to differences in setting, study population, and outcome definitions. Adherence and persistence rates varied substantially between CVD groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results were broadly consistent with several observational studies conducted in Australia 11 , 17 , 27 and other jurisdictions internationally, 8 , 25 , 31 although not directly comparable due to differences in setting, study population, and outcome definitions. Adherence and persistence rates varied substantially between CVD groups.…”
Section: Discussionsupporting
confidence: 90%
“…We also found lower adherence among anticoagulant and antiplatelet users, particularly 2 and 3 years after initiation. Although adherence rates for antihypertensives and statins are broadly consistent with previous Australian studies, there is less consistence in reported adherence rates for anticoagulants (42%–80%) 9 , 23 , 31 , 32 and antiplatelets (39%–79%). 31 , 32 However, persistence within the first year of initiation is usually high for antiplatelets (55%–89%) 13 , 14 and anticoagulants (69%–74%).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The treatment of choice to prevent another ischemic stroke is a long-term oral anticoagulant or antiplatelet strategy. However, many patients cannot take such drugs due to long-term contraindications, comorbidities, cognitive impairment, severe walking difficulties with frequent falls, and patient refusal [25,26]. The risk of death or addiction, as well as the risk of stroke recurrence in this group, is also not well known but must certainly be considered [25,26].…”
Section: Hemorrhagic Patients and Risk Of Ischemic Strokementioning
confidence: 99%
“…However, many patients cannot take such drugs due to long-term contraindications, comorbidities, cognitive impairment, severe walking difficulties with frequent falls, and patient refusal [25,26]. The risk of death or addiction, as well as the risk of stroke recurrence in this group, is also not well known but must certainly be considered [25,26]. The presence of ongoing bleeding causes a series of problems for patients who, at risk of thromboembolic events, take antiplatelet or anticoagulant therapy [27,28].…”
Section: Hemorrhagic Patients and Risk Of Ischemic Strokementioning
confidence: 99%